Optimization of Management Information System for Improving Hospital Performance - Wijayakusuma, Lucia Anindya; Rinawati, Rinawati (Jurnal sosial dan sains, 2025)
In the current era of digitalization, the implementation of a Hospital Management Information System (HMIS) has become an urgent necessity to improve service quality, accelerate administrative processes, and minimize errors in patient data management. Through an integrated system, hospitals can better coordinate human resources, logistics, and medical services. The optimization of HMIS does not solely focus on technological aspects but also includes improving human resource competencies, maintaining digital infrastructure, and enforcing internal policies that support digital transformation. One of the major challenges is the resistance of healthcare workers to the shift from manual to digital systems. Therefore, an adaptive and participatory managerial approach is needed to ensure that all hospital units accept and fully utilize information technology. An optimally implemented HMIS can have a positive impact on hospital operational efficiency, information transparency, and data-driven decision-making. Additionally, increased accuracy of medical data contributes to patient safety and performance evaluation of healthcare personnel. Thus, hospital management supported by a reliable information system becomes a vital foundation in delivering high-quality and sustainable healthcare services.